Medição do nível de maturidade do uso de tecnologia em um ambiente da indústria 4.0 - Schneider, Jaime (My University, 2019)
Manufacturing is in transformation at a speed never seen before. The speed and impact is such that one speaks of a new industrial revolution, the fourth, industry 4.0. This transformation is driven by enabling technologies, the technological backbone of industry 4.0. Technologies such as additive manufacturing, augmented reality, big data, collaborative or autonomous robotics, vertical and horizontal integration, internet of things, digital security, cloud computing and cyber physical systems, make up the technological pillars of i4.0. This work aims to measure the maturity in the use of these technologies in automotive companies. A maturity model was defined for each measured technology, having a model as reference. With the results obtained through the measurement of maturity, it was possible to identify which technologies are prominent in companies and where the gaps are, technologies that need attention and investments. The maturity levels were also compared among companies, which identified which companies have more mature results. With the analysis, it was possible to conclude that MES software can change the level of maturity of several technologies and also the companies need to have an environment of experimentation on technologies still unknown to them.
A manufatura está em transformação em uma velocidade nunca antes vista. A velocidade e o impacto é tal que se fala numa nova revolução industrial, a quarta, a indústria 4.0. Essa transformação é impulsionada por tecnologias facilitadoras, os pilares tecnológicos da indústria 4.0. Tecnologias como manufatura aditiva, realidade aumentada, big data, robótica colaborativa ou autônoma, integração vertical e horizontal, internet das coisas, segurança digital, computação na nuvem e sistemas ciber físicos, compõem os pilares tecnológicos da i4.0. Este trabalho tem como objetivo medir a maturidade no uso dessas tecnologias em empresas do ramo automotivo. Para a medição foi definido um modelo de maturidade para cada tecnologia medida, tendo um modelo como referência. Com os resultados obtidos através da medição de maturidade foi possível identificar quais tecnologias de destaque nas empresas e onde estão as lacunas, tecnologias que necessitam de atenção e investimentos. Os níveis de maturidade também foram comparados entre as empresas. Com isso se identificou quais empresas apresentam resultados mais maduros. Com as análises realizadas foi possível concluir que um software de MES pode mudar o nível de maturidade de várias tecnologias e também a necessidade das empresas em se ter um ambiente de experimentação de tecnologias ainda por elas desconhecidas.
Keywords: Automação industrial; Modelos de capacitação e maturidade (Software); Sistemas de Execução de Fabricação; Inovações tecnológicas; Indústria automobilística; Industrial automation; Training and Maturity Models (Software); Manufacturing Execution Systems; Technological Innovations; The auto industry